Electronic device use and its adversities among BPH students of Kathmandu valley - Sharma, Puja; Singh, Birendra Kumar; Neupane, Maryada; Shrestha, Noora; Chand, Prapti (International Journal Of Community Medicine And Public Health, 2024)
Background: Electronic devices here means devices like computer, laptop, smart phones, e-games etc. Recently the ownership, use and time-spent on electronic devices has increased dramatically on all age groups for the purpose of communication, entertainment, education, work, etc. and mostly adults are dependent on these devices. Methods: A descriptive cross sectional was done among 248 BPH students of Kathmandu valley. Four colleges were selected through lottery method and 62 students of 1st, 2nd and 3rd year were conveniently selected from each college by disproportionate stratified sampling. Semi-structured self-administered questionnaire was used to collect data which was analysed in SPSS version 21.0 and interpreted using bivariate test. Results: All the respondents owned at least one electronic device. Smart phones were found to be the mostly used electronic device and entertainment was the main purpose for which the devices were used. 10.5% showed range of health adversities in relation to electronic device use with eye symptoms being the most common adversity. 80% were found to use electronic device before going to bed which was associated with the sleep quality of the respondents. Conclusions: This study concluded that time-spent on electronic device is high and using electronic devices before bed time was significantly associated with the sleep quality. Not just sleep quality but excessive use of these devices for long run had the risk of developing health effects like headache, eye, ear and musculoskeletal symptoms and few had mild health effects.